Effect of Oxygen on Phosphodiesterases (PDE) 3 and 4 Isoforms and PKA Activity in the Superior Cervical Ganglia - Nunes, Ana Rita (2012)
The cAMP-protein kinase A (PKA) signaling pathway is involved in regulating the release of transmitters from neurons and other cells. Multiple phosphodiesterase (PDE) isoforms regulate this pathway, however, the pattern of isoform expression and stimulus response across tissues has not been fully characterized. Using fluorescent resonance energy transfer (FRET)-based imaging in primary superior cervical ganglia (SCG) neurons and real-time qPCR, we explored the role of PDE3 and PDE4 isoforms and oxygen tension in the activation of PKA and changes in gene expression. These primary neurons were infected with an adenovirus containing A-Kinase activity reporter (AKAR3) and assayed for responses to PDE inhibitors: rolipram (ROL, 1 μM), milrinone (MIL, 10 μM) and IBMX (100 μM), and adenylyl cyclase activator forskolin (FSK, 50 m M). Different PDE activity patterns were observed in different cells: high PDE4 activity (n = 3), high PDE3 activity (n = 3) and presence of activity of other PDEs (n = 3). Addition of PKA inhibitor H89 (10 μM) completely reversed the response. We further studied the effect of oxygen in the PKA activity induced by PDE inhibition. Both normoxia (20%O(2)/5%CO(2)) and hypoxia (0%O(2)/5%CO(2)) induced a similar increase in the FRET emission ratio (14.5 ± 0.8 and 14.7 ± 0.8, respectively). PDE3a, PDE4b and PDE4d isoforms mRNAs were highly expressed in the whole SCG with no modulation by hypoxia. Conclusion: Using a FRET-based PKA activity sensor, we show that primary SCG neurons can be used as a model system to dissect the contribution of different PDE isoforms in regulating cAMP/PKA signaling. The differential patterns of PDE regulation potentially represent subpopulations of ganglion cells with different physiological functions.